PERSEPSI SISWA TERHADAP PENILAIAN AKHIR SEMESTER MATEMATIKA BERBASIS OFFICE 365 DI KABUPATEN SINJAI - Irmayanti Irmayanti; Sri Wahyuni; Fitriani Fitriani (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2021)
This study aims to describe students' perception of the final assessment of the office 365-based mathematics semester in Sinjai District. This research uses a quantitative approach with a survey method. Descriptive research was selected to obtain exploratory data on students' perception of a final assessment of mathematics semester via office 365 in Sinjai District. The population of this study amounted to 137 people, namely all students of grade VIII, with a response rate of 100%. The sampling used is purposive sampling to get feedback on the final assessment of the math semester via office 365 that has been followed during the Covid-19 pandemic. Data collection techniques are using questionnaires distributed through a google form. Perception assessment is carried out by referring to 2 aspects, namely the flexibility aspect of applications and facilities and infrastructure. The flexibility section of the end-of-semester assessment application consists of 7 points of the statement which include: fun, concentration, enthusiasm, ease of access, timeliness of work, ease of understanding of questions, opportunities to find answers on the internet. Meanwhile, the second part consists of 3 positive statements that measure students' perception of the aspects of facilities and infrastructure used in the implementation of the final semester assessment online. The results showed that the flexibility aspect of the application obtained a perception level of 79% and the infrastructure aspect obtained a perception level of 86%. This percentage shows the feasibility or success of the final assessment of the office 365-based mathematics semester in Sinjai Regency. Overall, it can be concluded that students' perception of the final assessment of office 365-based mathematics semester in Sinjai District is positive with a perception rate of 83%.